Efeitos agudos de interrupções do comportamento sedentário com exercício isométrico nos indicadores de saúde cardiovascular de adultos: ensaio cruzado randomizado - Silva, Gustavo Oliveira da (2021)
The aim of this study was to analyze the acute effects of sedentary behavior breaks using isometric leg extension exercise in comparison to walking breaks and to uninterrupted sitting time on the cardiovascular health parameters of healthy adults. This was a randomized crossover trial, where the target population of the present study was comprised of healthy sedentary subjects above 18 years of age. The participants performed, in randomized order, three 3-hour experimental conditions (Control, Isometric leg extension exercise and walking breaks), where the order of the experimental conditions was determined through simple automatic randomization. On the isometric and walking conditions the participants performed isometric leg extension exercise and walking breaks every 30 min, and on the control condition remained seated without breaks. Before and after this period vascular function (primary outcome), blood pressure and cardiac autonomic modulation (secondary outcomes) were measured. Seventeen subjects completed the three experimental conditions (11 women; 29 ± 10 years). The results did not indicate statistically significant effects on vascular function between the experimental conditions (p>0,05 for all). Also, no significant differences were observed for systolic blood pressure or diastolic blood pressure between the experimental conditions (p>0,05 for all). Heart rate variability did not present significant effects between the experimental conditions (p>0,05 for all). In conclusion, isometric leg extension breaks do not seem to lead to significant changes on cardiovascular health parameters of adults in comparison to walking breaks or uninterrupted sitting time.